2009
DOI: 10.1186/1752-1947-3-115
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Euphorbia lathyris latex resulting in alkaline chemical injury: a case report

Abstract: IntroductionWe report the case of a patient with extreme pain following accidental exposure to the latex of Euphorbia lathyris.Case presentationA 76-year-old Caucasian woman attended the ophthalmology department with acute severe bilateral eye pain. This occurred immediately after having pulled a weed out of her garden with her bare hands. She recalled having subsequently rubbed her eyes. The offending plant, was brought into hospital and was identified as the Caper Spurge (Euphorbia lathyris). Her ocular pH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 3 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Ophthalmological examination a few hours later showed only a mild conjunctival lesion. As compared to the case reported by Ioannidis et al [13], flushing with Diphoterine® solution resulted in a less severe lesion and rapid pain relief. Donoghue [5] compared the efficacy of Diphoterine® solution with that of water for decontamination of alkaline chemical splashes in a clinical study involving 180 workers.…”
Section: Diphoterine® Solution Has Multiple Methods Of Actionmentioning
confidence: 65%
See 1 more Smart Citation
“…Ophthalmological examination a few hours later showed only a mild conjunctival lesion. As compared to the case reported by Ioannidis et al [13], flushing with Diphoterine® solution resulted in a less severe lesion and rapid pain relief. Donoghue [5] compared the efficacy of Diphoterine® solution with that of water for decontamination of alkaline chemical splashes in a clinical study involving 180 workers.…”
Section: Diphoterine® Solution Has Multiple Methods Of Actionmentioning
confidence: 65%
“…Ioannidis et al [13] reported the case of a 76-year-old man with eye injury due to exposure to the latex of the Euphorbia lathyris plant. Despite flushing with 8 liters of normal saline followed by treatment with dexamethasone and cicatrizing eye drops, the patient developed a corneal ulcer and severe pain which necessitated a 3-day hospitalization.…”
Section: Diphoterine® Solution Has Multiple Methods Of Actionmentioning
confidence: 99%
“…Another interesting report of Euphorbia toxicity involved the species Euphorbia lathyris 9. In that case, the authors reported that the patient’s ocular pH was alkaline which resulted in alkaline chemical injury as a result of exposure to the plant sap.…”
Section: Discussionmentioning
confidence: 99%
“…The patient, an avid gardener, remarked several times that the plant she had been pulling was of the Euphorbia genus. Further investigation into Euphorbia exposure revealed several references in the literature describing ocular toxicity and elevated pH secondary to exposure to the sap from this plant 9. The pH was measured in each eye and found to be 9 oculus dexter and 8 oculus sinister.…”
Section: Case Reportmentioning
confidence: 98%
“…This species has previously been associated with alkali chemical injury and extreme pain. 1 Given its common use as ornamental houseplant and its presentation as a weed in UK gardens, this discussion aims to increase awareness among medical staff, nurses and gardeners and act as a reminder to implore about gardening history.…”
mentioning
confidence: 99%